PENGGUNAAN METODE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Ikhwanul Muslimin (Majelis Pendidikan Aceh, 2018)
The use of appropriate methods in the learning process will increase students' motivation and interest in learning. but the state of the field Based on the initial observation of the field at the school MIN 16 Aceh Besar on the thematic lesson IPS teachers still use the lecture method, so that student learning outcomes do not increase. It is known that the lecture method used is no longer appropriate with the current development for all IPS materials, because this method has weaknesses among them that is, can cause students to be bored to learn, so that student learning outcomes are not increasing and not effective.. The purpose of this learning is to know the teacher activity and student's response to the application of Mind Mapping learning method on IPS subjects to improve students' learning motivation in grade IV MIN 16 Aceh Besar. This research is a class action research (PTK) consisting of several stages of planning, implementation, action and reflection with the subject of research is fourth grade students MIN 16 Aceh Besar, amounting to 28 students. Data collection techniques used: observation sheets (teacher and student), post-test questions and student response questions, and then analyzed using the percentage formula. The results showed that teacher activity in cycle I was 3.11% and increased in cycle II to 4.16%. Student activity in the first cycle reached 3.25% and increased in cycle II to 4.00%. As for the students response to Mind Mapping method there are 7 questions that have 100% of respondents from 12 questions that have good response. Based on the results of the research, it can be concluded that the use of Mind Mapping method is very suitable to be used in improving motivation to learn fourth grade students MIN 16 Aceh Besar